On the limits of hedging inflation risk in investment portfolios - Damiaan H. J. Chen; Roel Beetsma; Sweder van Wijnbergen (Tinbergen Institute, 2025)
We explore to what extent real returns on investment portfolios can be hedged against inflation risk by using existing financial market instruments. We find that inflation-linked bonds offer only limited protection against inflation risk and that nominal debt and stocks play at least comparable roles in this respect. These findings apply to both a static and a dynamic setting. The demonstrated limits of hedging inflation risk are of particular relevance for long-term investors, such as pension funds with participants concerned about the real value of their pension benefits.
Keywords: C61; E21; G11; G23; 330; unhedgeable inflation risk; incomplete markets; welfare loss; meanvariance frontiers; minimum risk portfolio; nominal and index-linked bonds